2021
DOI: 10.1530/erc-20-0507
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity and markers of inflammation during and after (neo-) adjuvant cancer treatment

Abstract: Exercise training has been hypothesized to lower the inflammatory burden for patients with cancer, but the role of exercise intensity is unknown. To this end, we compared the effects of high-intensity (HI) and low-to-moderate intensity (LMI) exercise on markers of inflammation in patients with curable breast, prostate and colorectal cancer undergoing primary adjuvant cancer treatment in a secondary analysis of the Phys-Can randomized trial (NCT02473003). Sub-group analyses focused on patients with breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…As shown in other cancer types, the therapeutic benefits of HIIT on HRQoL and fatigue may be mediated by improvements in aerobic capacity [ 77 ] and in a short time frame as the perioperative phase and the prescription of a higher exercise intensity could be a relevant factor to achieve central and peripheral physiological adaptations [ 78 , 79 , 80 ]. Furthermore, higher exercise intensities appear to protect against chemotherapy-related inflammation [ 81 ], a mechanism involved in the pathogenesis of fatigue [ 82 ], which could be clinically relevant for patients eligible to adjuvant treatment after surgery. This rationale is supported by a large clinical trial which found that a combination of high-intensity aerobic and resistance exercise was significantly more effective to reduce physical fatigue compared to low-to-moderate-intensity exercise in cancer patients undergoing (neo-)adjuvant treatment [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in other cancer types, the therapeutic benefits of HIIT on HRQoL and fatigue may be mediated by improvements in aerobic capacity [ 77 ] and in a short time frame as the perioperative phase and the prescription of a higher exercise intensity could be a relevant factor to achieve central and peripheral physiological adaptations [ 78 , 79 , 80 ]. Furthermore, higher exercise intensities appear to protect against chemotherapy-related inflammation [ 81 ], a mechanism involved in the pathogenesis of fatigue [ 82 ], which could be clinically relevant for patients eligible to adjuvant treatment after surgery. This rationale is supported by a large clinical trial which found that a combination of high-intensity aerobic and resistance exercise was significantly more effective to reduce physical fatigue compared to low-to-moderate-intensity exercise in cancer patients undergoing (neo-)adjuvant treatment [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as the immune system undergoes systematic changes from pre- to post-birth ( 18 , 19 ) and during aging ( 20 , 21 ), the knowledge taken from the immune response of adult cancer patients after exercise may not be directly transferable to pediatric cancer patients. The type, frequency, duration, and intensity of exercise could also affect the immune system in different ways ( 22 ). Therefore, research studies focusing on how exercise affects the pediatric immune system of cancer patients is a relevant research question.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that the results of the present study may also be applied to clinical populations. However, there are some considerations, including the greater possibility of acute illness across an intervention and variability in health status (e.g., glycemic control in diabetics ( Collier et al, 2008 ), treatment type and duration in oncology populations ( Schauer et al, 2021 )). Therefore, whilst considering whether interventional change of future trials exceeds the total error of the present study may assist in determining whether change is real, it is important to do so with the awareness that error may be greater among those with different clinical presentation from beginning to end of an intervention.…”
Section: Discussionmentioning
confidence: 99%